Performance Evaluation of Computer Campus Network Segments - Antonyuk, Ya.M. (Управляющие системы и машины, 2018)
The task of evaluating the performance of computer networks and their segments is considered - one of the main issues of the formation and functioning of modern campuses, educational spaces and corporate cloud solutions. To measure the characteristics of network performance, certain measurements were made on a sequence of packets arriving at some interface of a network device. Two types of existing measurements in the network are compared: active measurements and passive measurements. Conclusions are drawn about the possibility of measuring between any two nodes, or points, of the network based on preliminary data on the throughput capacity of individual network elements. The data transfer rate can be measured between any two nodes, or points, of a network, for example, between a client computer and a server, between the input and output ports of a router, and to analyze and configure the network to know the data on the throughput of individual network elements.